Nitric Oxide Limits the Expansion of Antigen-Specific T Cells in Mice Infected with the Microfilariae of Brugia pahangi - O'Connor, Richard A. (American Society for Microbiology, 2002)
Infection of BALB/c mice with the microfilariae (Mf) of the filarial nematode Brugia pahangi results in an antigen-specific proliferative defect that is induced by high levels of NO. Using carboxyfluorescein diacetate succinimydl ester and cell surface labeling, it was possible to identify a population of antigen-specific T cells from Mf-infected BALB/c mice that expressed particularly high levels of CD4 (CD4(hi)). These cells proliferated in culture only when inducible NO synthase was inhibited and accounted for almost all of the antigen-specific proliferative response under those conditions. CD4(hi) cells also expressed high levels of CD44, consistent with their status as activated T cells. A similar population of CD4(hi) cells was observed in cultures from Mf-infected gamma interferon receptor knockout (IFN-γR(−/−)) mice. Terminal deoxynucleotidyltransferase-mediated dUTP-biotin nick end labeling staining revealed that the CD4(+) T cells from Mf-infected wild-type mice were preferentially susceptible to apoptosis compared to CD4(+) T cells from IFN-γR(−/−) mice. These studies suggest that the expansion of antigen-specific T cells in Mf-infected mice is limited by NO.